2011
DOI: 10.1093/humrep/der115
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone regulate expression of the endothelins in the rhesus macaque endometrium

Abstract: Our results indicate that estrogen and progesterone regulate the EDN family during the menstrual cycle. The changes in the EDN paracrine system during the mid-secretory phase may indicate a role for EDN during embryo implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…There is increasing evidence that NF-κB signaling is an important player in cancer development and progression 23 . NF-κB signaling in cancer cells can be activated by factors such as IL-1β, TNFα and IL-8, IL-6 and MCP-1 secreted by cells in the microenvironment of the tumor, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that NF-κB signaling is an important player in cancer development and progression 23 . NF-κB signaling in cancer cells can be activated by factors such as IL-1β, TNFα and IL-8, IL-6 and MCP-1 secreted by cells in the microenvironment of the tumor, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…ATP6V0A4 mediates invasion of breast cancer cell lines in the transwell Matrigel assay (Hinton et al, 2009). EDN3 has been suggested as a tumor suppressor gene in the human mammary gland (Wiesmann et al, 2009) and its expression was shown to be regulated by estrogen and progesterone in the rhesus macaque (Keator et al, 2011). LTF (Lactotransferrin) is an estrogen-inducible gene (Das et al, 1998; Ghosh et al, 1999; Moggs et al, 2004; Stuckey et al, 2006); its protein product exists in high concentration in human milk (Hakansson et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA (1 mg) was reverse transcribed into cDNA, in the presence of random hexamer primers (Promega Corporation, Madison, WI, USA) using an Omniscript RT kit (Qiagen). Real-time PCRs were on a 7500 Fast Real-time PCR System (ABI; Applied Biosystems, Carlsbad, CA, USA) as described previously (Keator et al, 2011). Real-time PCRs were performed in duplicate on 2 ml of diluted (1:20) cDNA and compared against a five-point standard curve of pooled endometrial cDNA.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Real-time PCRs were performed in duplicate on 2 ml of diluted (1:20) cDNA and compared against a five-point standard curve of pooled endometrial cDNA. Each reaction contained 250-nM TaqManw probe specific for rhesus macaque MMP-26 (FAM-labeled) and probe (VIC-labeled) specific for the ribosomal protein gene RPL32 or mitochondrial ribosomal protein S10, described previously (Keator et al, 2011). The reactions contained 900-nM MMP-26 or 300-nM housekeeping gene sense and antisense primers and 5 ml of 2× Fast Universal PCR Master Mix (ABI).…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation